Towards a modular toolkit for strategic technology management. (13th August 2012) - Phaal, Robert; Kerr, Clive; Oughton, Dominic; Probert, David
Many strategic technology management methods and tools have been proposed and deployed by academics and practitioners. Each approach, with its advantages and disadvantages, provides a particular perspective for supporting understanding, analysis, decision and action. Many approaches overlap in function, the interfaces with other methods are not clear, and many variants of tools are often available with little guidance provided for their application. As a step towards the construction of a flexible toolkit for supporting strategic technology management, this paper sets out a workshop–based approach that comprises functional modules that can be combined to address a range of management challenges.